Bone Mineral Density and the Risk of Hip and Knee Osteoarthritis: The Johnston County Osteoarthritis Project. Issue 12 (2nd November 2017) - Barbour, Kamil E.; Murphy, Louise B.; Helmick, Charles G.; Hootman, Jennifer M.; Renner, Jordan B.; Jordan, Joanne M.
Abstract : Objective: To address knowledge gaps regarding the relationship between bone mineral density (BMD) and incident hip or knee osteoarthritis (OA); specifically, lack of information regarding hip OA or symptomatic outcomes. Methods: Using data (n = 1, 474) from the Johnston County Osteoarthritis Project's first (1999–2004) and second (2005–2010) followup of participants ages ≥45 years, we examined the association between total hip BMD and both hip and knee OA. Total hip BMD was measured using dual x‐ray absorptiometry, and participants were classified into sex‐specific quartiles (low, intermediate low, intermediate high, and high). Radiographic OA (ROA) was defined as development of Kellgren/Lawrence grade ≥2. Symptomatic ROA (sROA) was defined as onset of both ROA and symptoms. Weibull regression modeling was used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs). Results: Median followup time was 6.5 years (range 4.0–10.2 years). In multivariate models, and compared with participants with low BMD, those with intermediate high and high BMD were less likely to develop hip sROA (HR 0.52 [95% CI 0.31–0.86] and 0.56 [95% CI 0.31–0.86], respectively; P = 0.024 for trend); high BMD was not associated (HR 0.69 [95% CI 0.45–1.06]) with risk of hip ROA. Compared with participants with low BMD, those with intermediate low and intermediate high total hip BMD were more likely to develop knee sROA (HR 2.15 [95% CI 1.40–3.30] and 1.65 [95% CI 1.02–2.67], respectively; P = 0.325 for trend); similar associations were seen with knee ROA. Conclusion: Our findings suggest that higher BMD may reduce the risk of hip sROA, while intermediate levels may increase the risk of both knee sROA and ROA.